Design of perovskite thermally co-evaporated highly efficient mini-modules with high geometrical fill factors - Li, Jia (2021)
Perovskite solar cells (PSCs) have emerged as a promising technology for next-generation photovoltaics thanks to their high power-conversion-efficiency (PCE). Scaling up PSCs using industrially compatible processes is a key requirement to make them suitable for a variety of applications. Herein, large-area PSCs and perovskite solar modules (PSMs) are developed based on co-evaporated MAPbI3 using optimized structures and active area designs to enhance PCEs and geometrical fill factors (GFFs). Small-area co-evaporated PSCs (0.16 cm2) achieve PCE over 19%. When the PSCs are scaled-up, the thin films high quality allows them to maintain consistent Voc and Jsc, while their fill factors (FF), which depend on the substrate sheet resistance, are substantially compromised. However, PSCs with active areas from 1.4 to 7 cm2 show a substantially improved FF when rectangular designs with optimized length to width ratios are used. Reasoning these results in the PSM design with optimal subcell size and for specific dead areas, a 6.4 cm2 PSM is demonstrated with a record 18.4% PCE and a GFF of ≈91%. Combining the high uniformity of the co-evaporation deposition with active areas design, it is possible to scale up 40 times the PSCs with PCE losses smaller than 0.7% (absolute value).